+0  
 
+2
319
2
avatar+21 

This Is the last thing i need help with today, Anything is greatly appreciated as my mind is blank ATM. sad

 Dec 13, 2017
 #1
avatar+98196 
+2

Average Rate of change  =

 

[ f(8)   - f(0)  ]   / [  8  - 0 ]

 

f(8)  = [  2(8)  - 1]  / [ 3(8)  + 5]   =  15/ 29

f(0)  =  [ 2(0) - 1]  /  [ 3(0)  + 5 ]  =  - 1/5

 

So....average rate of change is

 

[ 15/29  -  -1/5 ]  /  8  =

 

[ 15/29  + 1/5 ]  /  8

 

[ ( 75 + 29)  / 145 ] / 8  =

 

[ 104] / [ 145 * 8  ]  =

 

13 / 145

 

 

cool cool cool

 Dec 13, 2017
 #2
avatar+21 
+1

Thank You @CPhill

 Dec 13, 2017

34 Online Users

avatar
avatar
avatar
avatar
avatar
avatar